Bone bending strength and BMD of female athletes in volleyball, soccer, and long-distance running - Roche-Rangel, J.; Liang, M. T. C.; Tsai, A. H.; Auslander, A. T.; Robles, P.; Kwon, Y.-L.; Arnaud, S. B. (European Journal of Applied Physiology, 2023)
Purpose The purpose of the study was to determine whether sports training comprised of (1) high-impact loading sport in volleyball (VOL), (2) odd impact loading sport in soccer (SOC), and (3) low impact sport in distance running (RUN) were associated with tibial bending strength and calcaneus bone mineral density (BMD), and ulnar bending strength and wrist BMD.